2001
DOI: 10.1016/s0925-4773(00)00574-8
|View full text |Cite
|
Sign up to set email alerts
|

The tissue polarity gene nemo carries out multiple roles in patterning during Drosophila development

Abstract: Drosophila nemo was first identified as a gene required for tissue polarity during ommatidial development. We have extended the analysis of nemo and found that it participates in multiple developmental processes. It is required during wing development for wing shape and vein patterning. We observe genetic interactions between nemo and mutations in the Notch, Wingless, Frizzled and Decapentaplegic pathways. Our data support the findings from other organisms that Nemo proteins act as negative regulators of Wingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 63 publications
3
54
0
Order By: Relevance
“…The following fly strains were used: nmo DB24 (D. Bessette and E.M.V., unpublished); nmo adk1 and UAS-nmo C5-1e (Verheyen et al, 2001); nmo P (also referred to as nmo-lacZ) (Choi and Benzer, 1994); sd-Gal4 (sd SG29.1 ); UAS-Daxin A2-4 (Willert et al, 1999); UAS-flu∆arm and AyGal4.25-UAS-GFP.S65T (Ito et al, 1997;Zecca et al, 1996);vgGal4, Dll-lacZ, Ubi-GFP FRT 79D, ap-Gal4, dpp-lacZ (Morimura et al, 1996); 71B-Gal4, UAS-lacZ, zw3 m11 and UAS-DFz2N (Zhang and Carthew, 1998) and dsh v26 .…”
Section: Fly Strainsmentioning
confidence: 99%
See 2 more Smart Citations
“…The following fly strains were used: nmo DB24 (D. Bessette and E.M.V., unpublished); nmo adk1 and UAS-nmo C5-1e (Verheyen et al, 2001); nmo P (also referred to as nmo-lacZ) (Choi and Benzer, 1994); sd-Gal4 (sd SG29.1 ); UAS-Daxin A2-4 (Willert et al, 1999); UAS-flu∆arm and AyGal4.25-UAS-GFP.S65T (Ito et al, 1997;Zecca et al, 1996);vgGal4, Dll-lacZ, Ubi-GFP FRT 79D, ap-Gal4, dpp-lacZ (Morimura et al, 1996); 71B-Gal4, UAS-lacZ, zw3 m11 and UAS-DFz2N (Zhang and Carthew, 1998) and dsh v26 .…”
Section: Fly Strainsmentioning
confidence: 99%
“…Subsequent analysis has shown that Nemo functions in multiple tissues and has diverse roles in development. In addition to its effect on eye polarity, we have found that disruption of nmo results in changes in wing shape and size, wing vein specification, fertility and viability (Verheyen et al, 2001). nmo is essential for embryonic development as loss of maternal and zygotic nmo results in embryonic lethality characterized by patterning defects in the head and ventral denticle belts as well as disruption of apoptosis (Mirkovic et al, 2002).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Genetic studies revealed that homologs of NLK function as suppressors of the Wnt signaling pathway in the development of C. elegans and Drosophila. [1][2][3][4] A recent study showed that Wnt5a-Ca 2+ signaling, which is a negative regulator of Wnt, 5) can be an upstream activator of NLK for suppression of canonical Wnt-β-catenin signaling in the Xenopus system. 6) The target molecules of NLK in the Wnt-β-catenin pathway are conserved between worm and mammals.…”
mentioning
confidence: 99%
“…The signalling pathway is also regulated by the Nemo-like kinase (Nlk). Nlk is the mammalian homologue the Drosophila Nemo (nmo) Ser/Thr kinase, that is involved in apoptosis [16] and in multiple developmental processes [17] and was initially identified as a protein required for planar cell polarity in the developing Drosophila eye [18]. Nlk can be activated by the upstream MAP kinase kinase kinase (MAPKKK) family member transforming growth factor-␤ activated kinase-1 (Tak1) [19][20][21].…”
Section: ␤-Catenin Activates the Family Of T-cell Factor (Tcf) And Lymentioning
confidence: 99%